INOVASI PEMGEMBANGAN KURIKULUM PENDIDIKAN PESANTREN DI ERA DIGITAL - Sholeh Huda; Adiyono Adiyono (CV. ADIBA AISHA AMIRA, 2023)
This research uses a library research approach. This method is a type of research that is collected entirely from library findings or writing library references. Data is collected from various sources of reading, storing, analyzing, and classifying data to be able to draw reliable conclusions. Innovation or renewal of a curriculum needs to be done, considering that the curriculum as a means to achieve goals must adapt to the ever-changing and evolving development of society. Curriculum changes begin with fundamental conceptual changes, then followed by structural changes. This paper aims to examine and describe innovations in the development of pesantren education curriculum in the digital era. Pesantren education has an important role in shaping character and improving the quality of religious education. However, with technological advances and changes in educational demands, innovations are needed in the development of pesantren curriculum to answer the challenges of the digital era. Through literature study and conceptual analysis, this paper analyzes various innovations that can be made in the development of pesantren education curriculum in the digital era. In general, curriculum changes involve curriculum components, namely: a). changes in curriculum objectives, b). Changes in curriculum content and structure, c). Changes in curriculum strategies, d). Changes in curriculum facilities.